What narrative is told about recidivism in Latin America? A critical review of existing studies - Sanhueza Olivares, Guillermo Enrique (2023)
In theory, one of the purposes of prison sanctions is the resocialization of people who have been sentenced, with the expectation that they will not commit crimes again once they leave prison. However, the empirical reality in many Latin American countries shows high levels of criminal recidivism, which is problematic for the public security of the countries and because it questions an important assumption of the purposes of the prison sentence. Since the literature of developed countries indicates that criminal recidivism is caused by various factors, in this article we wanted to critically analyze what has been studied in the region in terms of criminal recidivism. For this, we carried out a systematic literature review of articles that addressed this topic. Our findings show that most of the studies are limited to small samples, in specific prisons, and with very different methodologies, making it difficult to generalize the results. Likewise, we found that most of the studies examined tend to present individual characteristics as the "central narrative" in the history of recidivism, omitting or hiding variables of a more structural or meso-social type (such as neighborhoods or the characteristics of prisons). where people served sentences), which may be suggesting a lack of public policy concern towards the issue and/or profound individualistic attributions in dealing with recidivism in the region.